Bacterial cellulose/Laponite composites as a potential new dressing with antibacterial properties - Silva, Jhonatan Miguel; Nunes, Nayara Carolina; Constantino, Vera Regina Leopoldo; Passos, Aline Ribeiro; Fontes, Marina Lima; Marcato, Priscyla Daniely; de Carvalho, Gustavo Senra G.; Brighenti, Fernanda Lourenção [UNESP]; de Oliveira, Analú Barros [UNESP]; Ferrisse, Túlio Morandin [UNESP]; da Silva Barud, Hernane (Elsevier, 2025)
Bacterial cellulose (BC) exhibits burst-release behavior in drug-delivery systems, which can lead to potentially harmful pharmacological effects. This study focused on nanocomposites prepared from BC and varying amounts of Laponite (Lap) clay to examine their ability to adsorb the antibiotic ciprofloxacin in water and to release the drug in a buffer solution. Scanning electron microscopy (SEM) images showed that the average diameter of the fibers increased with higher Laponite content, leading to fiber aggregation in the BC/Lap composites containing 1.8 -12.7 % (m/m) clay. X-ray diffraction (XRD) profile indicated that the increased clay content reduced the relative crystallinity of the organic membranes. Furthermore, the BC/Lap composites with 1.8–12.7 % clay demonstrated greater thermal stability compared to pristine BC. Regarding adsorption and release assays, the composites showed a higher affinity and loading capacity for the antibiotic compared to pristine BC. Specifically, the BC/Lap 7.7 % film could load approximately twice as much ciprofloxacin.